2018
DOI: 10.2298/tsci170323139j
|View full text |Cite
|
Sign up to set email alerts
|

Numerical investigation of magnetic nanofluids flow over rotating disk embedded in a porous medium

Abstract: Combined effects of thermal radiation and variable viscosity on a time-dependent boundary-layer flow of magnetic nanofluids over a rotating disk in the presence of the porous medium have been numerically investigated. To carry out the study, hydrocarbon based magnetic nanofluid containing magnetite Fe 3 O 4 particles of 10 nm with magnetic phase concentration of 10% has been taken. For numerical solutions of the modelled system containing the governing equation of the flow, a MATLAB tool ODE45 is employed with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 30 publications
1
19
0
Order By: Relevance
“…The validation of the findings adopted in the present study is shown in Table 2 by comparing the heat transfer rate with the published work by Joshi et al, 26 Maleque 49 and Sparrow and Gregg; 48 who studied the similar problems for the case of laminar flow of viscous incompressible magnetic nanofluid over the rotating disk. The comparison manifests outstanding agreement, and hence encouragement for Maple environment in the present study.…”
Section: Numerical Schemesupporting
confidence: 66%
See 3 more Smart Citations
“…The validation of the findings adopted in the present study is shown in Table 2 by comparing the heat transfer rate with the published work by Joshi et al, 26 Maleque 49 and Sparrow and Gregg; 48 who studied the similar problems for the case of laminar flow of viscous incompressible magnetic nanofluid over the rotating disk. The comparison manifests outstanding agreement, and hence encouragement for Maple environment in the present study.…”
Section: Numerical Schemesupporting
confidence: 66%
“…Moreover, the linearized magnetic equation of state, boundary layer approximation in the radial direction, and magnetic potential with magnetic dipole (m) are described as reported by the authors. 26,43 Furthermore, the flux induced by thermal radiation [45][46][47] (Rosseland estimation for the radiation) can be popularized as follows:…”
Section: Mathematical Problemmentioning
confidence: 99%
See 2 more Smart Citations
“…Turkyilmazoglu 23 focused on water‐based nanofluids and elaborated the impact of nanoparticles on heat transfer and flow pattern with a rotating disc. Moreover, Griffiths, 24 Ram et al, 25 Joshi et al, 26 and Bhandari and Husain 27 also worked on the problem related to the rotating disc.…”
Section: Introductionmentioning
confidence: 99%